International Conference on Innovative Computing and Communications Proceedings of ICICC 2020, Volume 1 - Gupta, Deepak; Khanna, Ashish; Bhattacharyya, Siddhartha; Hassanien, Aboul Ella; Anand, Sameer; Jaiswal, Ajay (Advances in Intelligent Systems and Computing, 2021)
XXIX, 1180 p. 608 illus., 464 illus. in color.